Venus Figurines of the European Paleolithic: Symbols of Fertility or Attractiveness?. (3rd January 2012) - Dixson, Alan F.; Dixson, Barnaby J.
Abstract : The earliest known representations of the human female form are the European Paleolithic "Venus figurines, " ranging in age from 23, 000 to 25, 000 years. We asked participants to rate images of Paleolithic figurines for their attractiveness, age grouping and reproductive status. Attractiveness was positively correlated with measures of the waist-to hip ratio (WHR) of figurines, consistent with the "sexually attractive symbolism" hypothesis. However, most figurines had high WHRs (>1.0) and received low attractiveness scores. Participants rated most figurines as representing middle-aged or young adult women, rather than being adolescent or older (postmenopausal). While some were considered to represent pregnant women, consistent with the "fertility symbol" hypothesis, most were judged as being non-pregnant. Some figurines depict obese, large-breasted women, who are in their mature reproductive years and usually regarded as being of lower attractiveness. At the time these figurines were made, Europe was in the grip of a severe ice age. Obesity and survival into middle age after multiple pregnancies may have been rare in the European Upper Paleolithic. We suggest that depictions of corpulent, middle-aged females were not "Venuses" in any conventional sense. They may, instead, have symbolized the hope for survival and longevity, within well-nourished and reproductively successful communities.